Pengaruh Konsentrasi Ekstrak Tanaman Meniran (Phillanthus niruri L.) Dalam Melarutkan Kalsium - Winarti, Winarti; Nuryanti, Siti; Said, Irwan (Universitas Tadulako, 2014)
Research on the solubility of calcium has been conducted using meniran (phillanthus niruri L.) plant extracts by varying concentrations. This research was conducted by laboratory experiments using meniran plant extracts as samples in dissolving calcium phosphate as a substitute for kidney stones. Meniran is a type of acidic herbal plant extract which contains flavonoids and potassium, so it can dissolve calcium. This study was conducted to determine the most effective concentration of meniran plant extracts from the variation concentration (2%, 4%, 6%, 8% and 10%) in dissolving calcium, and also to determine the effectiveness of this extract compared to Batugin Elixir and distilled water. Determination of the concentration of dissolved calcium in meniran plant extracts was done by a flame photometer. The results showed concentration of 10% of meniran plant extract was effective in dissolving calcium whichwas equal to 46.1 ppm. However, Batugin Elixir was more effective in dissolving calcium with a concentration equal to 58.2 ppm, while distilled water can dissolve the calcium only equal to 4.8 ppm.